2013
DOI: 10.5588/ijtld.12.0933
|View full text |Cite
|
Sign up to set email alerts
|

Yield of contact tracing from pediatric tuberculosis index cases in Gaborone, Botswana

Abstract: SETTING: Contact tracing using pediatric index cases has not been adequately investigated in high tuberculosis (TB) and human immunodeficiency virus (HIV) prevalence settings. OBJECTIVE: To determine the yield of contact tracing in household contacts of pediatric TB index cases in Botswana. DESIGN: Index cases included all pediatric (age ⩽13 years) TB admissions from January 2009 to December 2011 to Botswana’s largest referral hospital. A contact tracing team identified cases, conducted home visits, sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 9 publications
2
22
2
Order By: Relevance
“…As the majority of child TB is not bacteriologically confirmed, we garner important information by comparing NNS using all forms of TB as our outcome and demonstrate that the NNS was 40% greater for a child index case compared to an adult index case. Previously reported source case investigations including children hospitalized for TB in TB/HIV high burden settings have demonstrated 2–3% yield [22, 23]. Similarly, the yield of source case investigation originating from index cases under five years of age participating in our program was 2.5%.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…As the majority of child TB is not bacteriologically confirmed, we garner important information by comparing NNS using all forms of TB as our outcome and demonstrate that the NNS was 40% greater for a child index case compared to an adult index case. Previously reported source case investigations including children hospitalized for TB in TB/HIV high burden settings have demonstrated 2–3% yield [22, 23]. Similarly, the yield of source case investigation originating from index cases under five years of age participating in our program was 2.5%.…”
Section: Discussionmentioning
confidence: 50%
“…As we were unable to measure our programs coverage rate of index cases, we cannot estimate the full potential of contact tracing in our setting if coverage rate was to increase. Similar to many other contact tracing studies [22, 23, 30], we were unable to follow contacts longitudinally and measure the impact of our intervention on TB prevention.…”
Section: Discussionmentioning
confidence: 99%
“…We found that child contacts younger than five years had the highest risk of being diagnosed with TB. Although some studies and systematic reviews have reported that the yield among children is comparable to that seen in adult contacts [5,25], some studies have shown that there is a high prevalence of TB in children among contacts, as seen in our study [26,27]. This can be explained by the fact that young children are more likely to stay at home, which can increase exposure time especially if the index cases are their first-degree relatives [28].…”
Section: Discussioncontrasting
confidence: 48%
“…Here 31% of households had at least 1 additional previously undiagnosed person with either latent or active TB disease 13 .…”
Section: Discussionmentioning
confidence: 99%